2016
DOI: 10.1183/13993003.01389-2015
|View full text |Cite
|
Sign up to set email alerts
|

Fertility outcomes in asthma: a clinical study of 245 women with unexplained infertility

Abstract: Evidence is increasing of an association between asthma and aspects of female reproduction. However, current knowledge is limited and furthermore relies on questionnaire studies or small populations. In a prospective observational cohort study to investigate whether time to pregnancy, the number of fertility treatments, and the number of successful pregnancies differ significantly between women with unexplained infertility with and without asthma.245 women with unexplained infertility (aged 23-45 years) underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…In a study from North America published more than 20 years ago focusing on women with ovulatory dysfunction as the cause of infertility, compared to women admitted to hospital for a life birth, Grodstein et al [6] reported that use of asthma medication for more than 6 months increased the risk of infertility, and, furthermore, the risk of ovulatory infertility was higher in women using beta2-agonists, whereas no significant increase was found in women treated with theofyllin. As described above, the study by Gade et al [5] revealed that among women with unexplained infertility, women with asthma were less likely to conceive than non-asthmatic women following fertility treatment, especially in women over 35 years of age with pregnancy rates were 26% and 57%, respectively, for asthmatic and non-asthmatic women. Overall, women not conceiving during the observation period were significantly older than those with successful fertility treatment (37 vs. 35 years of age).…”
Section: Reduction In Fertility and Fertility Treatmentmentioning
confidence: 89%
See 1 more Smart Citation
“…In a study from North America published more than 20 years ago focusing on women with ovulatory dysfunction as the cause of infertility, compared to women admitted to hospital for a life birth, Grodstein et al [6] reported that use of asthma medication for more than 6 months increased the risk of infertility, and, furthermore, the risk of ovulatory infertility was higher in women using beta2-agonists, whereas no significant increase was found in women treated with theofyllin. As described above, the study by Gade et al [5] revealed that among women with unexplained infertility, women with asthma were less likely to conceive than non-asthmatic women following fertility treatment, especially in women over 35 years of age with pregnancy rates were 26% and 57%, respectively, for asthmatic and non-asthmatic women. Overall, women not conceiving during the observation period were significantly older than those with successful fertility treatment (37 vs. 35 years of age).…”
Section: Reduction In Fertility and Fertility Treatmentmentioning
confidence: 89%
“…However, women with asthma prescribed any asthma therapy tended to have a lower prevalence of abnormal TTP compared to untreated women with asthma (24% and 31%, respectively). In a further prospective study by the same group [5], 245 women with unexplained infertility, including 81 women with current asthma, undergoing fertility treatment was followed. All enrolled women underwent clinical evaluation for asthma, including spirometry and bronchial challenge testing.…”
Section: Time To Pregnancy In Women With Asthmamentioning
confidence: 99%
“…GADE et al [3] found an association between untreated asthma (defined as no regular inhalers) and time to pregnancy, as well as between use of daily inhaled corticosteroid (ICS) and longer time to pregnancy, although it was not possible to differentiate between asthma severity per se and the level of treatment [3]. However, this was not found in a subsequent clinical study [7]. Recently, interesting data from the Screening for Pregnancy Endpoints (SCOPE) study have shown that women with self-reported asthma only using short-acting β 2 -agonists (SABAs) had prolonged time to pregnancy and reduced fertility [6], yet those with self-reported asthma who were prescribed ICS had no reduction in fertility.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that undertreatment of asthma with systemic inflammation may reduce fertility [6]. Given this data, women with asthma should be informed of the risk of reduced fertility especially if not on maintenance ICS therapy and particularly above 35 years of age [7,8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation